UTILIZATION SOFT STEM OF KEPOK BANANA WASTE (Musa paradisiaca formatypica) AS A BASIC MATERIAL FOR MAKING BIOETANOL WITH ACID HYDROLYSIS METHOD AND FERMENTATION (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Bioenergy, such as bioethanol, is one of the alternative options in order to fulfil the energy demands in the future. Bioethanol is ethanol which resulted from the fermentation process of glucose from natural sources that contains starch and cellulose. This research are aimed to utilize  soft stem of kapok banana (Musa paradisiaca formatypica), which known to have cellulose content approximately 64%, in order to produce bioethanol undergoes acid hydrolysis and bacterial fermentation using Clostridium acetobutylicum. There are two main variables that being investigate in this research such as, acid (HCl) volume of adding (varied from 15 mL, 20 mL, 25 mL, 30 mL, and 30 mL) and length of fermentation time ( 3, 6, 9, 12, and 15 days respectively). Results shown that the maximum concentration of cellulose in soft stem of kepok banana is 46.38% and the bioethanol concentration/volume were achieved on the addition of 15 mL acid chloride and optimum fermentation time of 6 days.
Keywords: bioethanol; soft stem of kepok banana; cellulose; Clostridium acetobutylicum